Enabling cell–cell communication via nanopore formation: structure, function and localization of the unique cell wall amidase AmiC2 of Nostoc punctiforme. (27th February 2016) - Büttner, Felix M.; Faulhaber, Katharina; Forchhammer, Karl; Maldener, Iris; Stehle, Thilo
Abstract : To orchestrate a complex life style in changing environments, the filamentous cyanobacterium Nostoc punctiforme facilitates communication between neighboring cells through septal junction complexes. This is achieved by nanopores that perforate the peptidoglycan (PGN) layer and traverse the cell septa. The N ‐acetylmuramoyl‐l ‐alanine amidase AmiC2 (Npun_F1846;EC 3.5.1.28 ) in N . punctiforme generates arrays of such nanopores in the septal PGN, in contrast to homologous amidases that mediate daughter cell separation after cell division in unicellular bacteria. Nanopore formation is therefore a novel property of AmiC homologs. Immunofluorescence shows that native AmiC2 localizes to the maturing septum. The high‐resolution crystal structure (1.12 Å) of its catalytic domain (AmiC2‐cat) differs significantly from known structures of cell splitting and PGN recycling amidases. A wide and shallow binding cavity allows easy access of the substrate to the active site, which harbors an essential zinc ion. AmiC2‐cat exhibits strong hydrolytic activity in vitro . A single point mutation of a conserved glutamate near the zinc ion results in total loss of activity, whereas zinc removal leads to instability of AmiC2‐cat. An inhibitory α‐helix, as found in the Escherichia coli AmiC E. coli structure, is absent. Taken together, our data provide insight into the cell‐biological, biochemical and structural properties of an unusual cell wall lytic enzyme that generates nanopores for cell–cell communication in multicellular cyanobacteria. The novel structural features of the catalytic domain and the unique biological function of AmiC2 hint at mechanisms of action and regulation that are distinct from other amidases. Database: The AmiC2‐cat structure has been deposited in the Protein Data Bank under accession number5EMI . Abstract : The unique N‐acetylmuramoyl‐L‐alanine amidase AmiC2 of Nostoc punctiforme facilitates communication of neighboring cells by formation of a nanopore array in newly formed septa. Our highly resolved crystal structure of the catalytic domain reveals intriguing differences compared to homologues amidases involved in daughter‐cell separation. Mutational and enzymatic analysis furthermore shows the importance of a bound zinc ion and the residue E578.